Post-COVID-19 syndrome and plastic surgery: case report of a patient with return of respiratory symptoms in the postoperative period of reduction mammaplasty - Thais De Sousa Gonçalves; Bruna Lago Chaves; Giovanna Lucieri Alonso Costa; Lia Patrus Bannet; Farid Hakme (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: As the concept of post-COVID-19 syndrome emerges, the negative result of an RT-PCR test is no longer enough to represent a patient’s complete clinical recovery. In this context, a question arises: what are the risks of performing surgery on a patient whom COVID-19 has already infected? Case Report: Female patient, 36 years, infected by COVID-19 in December 2020, showing mild symptoms. Once asymptomatic and with a negative RT-PCR test, she was submitted to a breast reduction surgery, in January 2021, through the inferior pedicle technique by Liacyr Ribeiro and Nipple-Areolar Complex (NAC) ascension by Letterman maneuver. On the first postoperative day, the patient developed respiratory symptoms, which continued throughout the postoperative period. Despite the unsatisfactory treatment of partial necrosis of the right NAC, the patient maintained respiratory and systemic symptoms suggestive of the return of COVID-19 in the late postoperative period. Discussion: Post-COVID-19 syndrome is defined as the persistence of symptoms of COVID-19, for at least 6 months, after the acute phase of infection. The syndrome’s pathophysiology is not completely elucidated; however, a relationship with the Mast Cell Activation Syndrome is proposed. In the report, we emphasize the chronological proximity between SARS-CoV-2 infection and the return of respiratory and systemic symptoms suggestive of post-COVID-19 syndrome and the need to know the possible symptoms and complications of this syndrome, especially in the context of postoperative. Conclusion: The need for a thorough preoperative analysis in patients with a clinical history of COVID-19 infection is evident since there is a greater risk of postoperative complications.